Deepithelialized glans reconfiguration (DeGRe) for distal hypospadias repair. Issue 1 (February 2021) - Alshammari, D.; Harper, L.
Summary: Introduction: Our objective was to present our experience with a novel technique for distal hypospadias repair consisting of deepithelialized glans reconfiguration. Patients and method: We reviewed the clinical data of all patients who underwent distal hypospadias using Deepithelialized Glans Reconfiguration between January 2015 and December 2019. We noted age at surgery, position of meatus, duration of urethral catheterization and hospitalization, as well as early and late complications. Standard postoperative care included follow-up examination at 1, 6 and 12 months. Successful repair was defined as a patient presenting with a straight penis with an apical meatus, no stricture nor fistula. Results: Sixty-seven patients were included. Average age at surgery was 12.5 months (6–23 months). All patients presented distal hypospadias (3 glanular, 61 coronal, 3 subcoronal). 36% of patients were operated as day case surgery. No intra-operative complications were recorded. Eleven patients did not complete the designated follow up. They attended the post-operative appointment at six months but not the one-year visit. All patients presented satisfactory urinary streams according to the parents. All parents were satisfied with the cosmetic appearance of their child's penis. Two patients presented with glans dehiscence (3%). The mean HOPE score for the last 10 patients was 47.4 ± 3.2 out of a maximum of 50. Discussion: Deepithelialized Glans Reconfiguration is a simple technique with satisfactory results. Though it has similarities with existing techniques, it contains specific aspects not described previously. Contrary to the MAGPI technique, there is no meatal advancement, no rotation of the glans wings, and it is the glans lateral and proximal to the meatus which is approximated in the midline. As opposed to the GAP procedure, there is no closure of the ventral aspect of the urethra. We rely on secondary healing within the glans to reconstruct the missing ventral aspect of the urethra. We reserve this technique for coronal hypospadias with a wide, deep glanular groove. Deepithelialization favours rapid healing of the glans wings on the midline. There is no formal urethroplasty. The limits to this study include lack of long-term (>1 year) follow-up and uroflow. Though careful observation did not identify fistulas, the absence of functional stenosis has to be more clearly evaluated at a later age. Finally, this technique is not suitable for the completely flat glans as it relies on being able to approximate the glans ridges in the midline. Conclusion: Deepithelialized Glans Reconfiguration is a simple technique which achieves good cosmetic results, without complications associated with meatal or urethral advancement or formal urethroplasty. Summary Figure Summary figure